Evolution and key technologies of 5G-oriented IP RAN - Xiaoming HE; Ping YUE; Quan LU; Yuanyang YIN (Dianxin kexue)
IP RAN need to adapt to the changes of 5G network architecture to meet the differentiated bearing requirements of eMBB,uRLLC and mMTC services defined by 5G.The network capabilities of “large bandwidth,low latency,flexible connection” are the basic requirements of IP RAN for 5G bearer.Firstly,the characteristics of 5G services and network architecture were analyzed,and the 5G-oriented IP RAN evolution scheme was proposed.Then,the key technologies of 5G-beared IP RAN were investigated and tested to provide support and suggestions for large-scale commercial deployment of 5G.